2012
DOI: 10.1007/s00213-012-2937-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking abstinence on smoking-reinforced responding, withdrawal, and cognition in adults with and without attention deficit hyperactivity disorder

Abstract: Rationale Individuals with attention deficit hyperactivity disorder (ADHD) have a more difficult time quitting smoking compared to their non-ADHD peers. Little is known about the underlying behavioral mechanisms associated with this increased risk. Objectives This study aims to assess the effects of 24-h smoking abstinence in adult smokers with and without ADHD on the following outcomes: smoking-reinforced responding, withdrawal, and cognitive function. Methods Thirty-three (n=16 with ADHD, 17 without ADHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 73 publications
(99 reference statements)
0
38
1
1
Order By: Relevance
“…This relationship between ADHD and greater nicotine withdrawal symptoms is supported by other studies. Female, but not male, smokers with ADHD had greater withdrawal symptoms (McClernon et al, 2011), and in other studies, smokers with ADHD showed great withdrawal symptoms and willingness to work harder for cigarette puffs (Kollins et al, 2013; Pomerleau et al, 2003). Furthermore, another study found that both male and female smokers with ADHD had a greater level of nicotine dependence than smokers without ADHD (Wilens et al, 2008).…”
Section: Nicotine’s Effects On Adhdmentioning
confidence: 63%
“…This relationship between ADHD and greater nicotine withdrawal symptoms is supported by other studies. Female, but not male, smokers with ADHD had greater withdrawal symptoms (McClernon et al, 2011), and in other studies, smokers with ADHD showed great withdrawal symptoms and willingness to work harder for cigarette puffs (Kollins et al, 2013; Pomerleau et al, 2003). Furthermore, another study found that both male and female smokers with ADHD had a greater level of nicotine dependence than smokers without ADHD (Wilens et al, 2008).…”
Section: Nicotine’s Effects On Adhdmentioning
confidence: 63%
“…Prior work suggests that regions within the brain's executive control network (eg, DLPFC, MF/CG) are vital for cognitive control (Fassbender et al, 2004;Krain et al, 2006), whereas regions within the default mode network (eg, PCC, vmPFC) are involved in self-referential and stimulus-independent thought processes that can compete with executive control functions Smith et al, 2009). Given the importance of outwardly focused attention and cognitive control in smoking behavior change (Ashare et al, 2013b;Kollins et al, 2013;Sutherland et al, 2012), we expected that short-term relapse would be predicted by reduced activation in DLPFC and MF/CG, and less suppression of activation in PCC and vmPFC, as assessed during a pre-quit abstinence challenge (vs smoking satiety).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, particularly during the first five days of abstinence, smokers with ADHD experienced greater craving, negative affect, physical symptoms, and habit withdrawal compared to smokers without ADHD and these abstinence effects were independent of changes in ADHD symptoms (McClernon et al, 2011). Finally, recent reports have demonstrated that higher levels of withdrawal and craving were associated with ADHD symptom level in laboratory (Ashare & Hawk, 2012; Kollins et al, 2013) and population-based (Ameringer & Leventhal, 2012) studies of smokers and in a clinical trial of those making a cessation attempt particularly after (vs. before) quit day (Berlin, Hu, Covey, & Winhusen, 2012). While extant findings provide support the ADHD-tobacco withdrawal relation, several features of this association require further attention.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, ADHD symptoms may be associated with certain smoking withdrawal symptoms (e.g., concentration problems) during regular smoking, which reflect baseline disturbances associated with the ADHD syndrome rather than withdrawal effects per se. Indeed, preliminary laboratory work using small samples has suggested certain aspects of withdrawal may be elevated in ADHD smokers regardless of abstinence status, but suggest that there may not be further increases during abstinence states (Kollins et al, 2013). Further, studies that do not contrast abstinent and non-abstinent states (Pomerleau et al, 2003) leave unclear whether withdrawal symptoms reported in smokers with elevated ADHD symptoms are true abstinence effects or simply reflect baseline levels of psychological disturbance.…”
Section: Introductionmentioning
confidence: 99%